Design of E-Library SD Negeri 11 Tanah Garam Kota Solok Based on Web: Perancangan E-Library SD Negeri 11 Tanah Garam Kota Solok Berbasis Web - evi yulia susanti evi (Perkumpulan Doktor Indonesia Maju (PDIM), 2020)
Library in Public Elementary school 11 Tanah Garam Solok City quite achievement compared to other school libraries, with this e-library users can make it as a medium of information as well as a library promotion media for Elementary School level in Solok City. Data obtained from library from Public Elementary School 11 Tanah Garam Solok City, then the design of this e-library uses some supporting software, i.e. Bootstrap, PHP, MySQL, Xampp. From the results of this design e-library application makes it easy for library visitors to find the books you want without having to come to the library. Enough with the connection to the library with a computer connected to the internet network. Then with the e-library application it also helps librarians in book collection, visitor data collection.